A Miscarriage of History: The Case of Adria K. Lawrenceas Imperial Rule and the Politics of Nationalism: Anti-Colonial Protest in the French Empire (Global Journal of Human-Social Science, 2017)
Introduction-The writing of history, as always, has been subject to biases, most of the time from those who call the shots, but sometimes from factors so insidious that it is very difficult to isolate them. Books of history written by approved authorities as well as by independent ones, are replete with such examples I do not have space for in this work. I need, however, to draw a line between deliberately sidestepped factors and those that, for one reason or another, have been omitted. My concern in this paper is to highlight the factors that, willingly or not, are overlooked by the author of the book under focus for what I think are ideologically motivated reasons.